The Protective Effects of Pulsed Magnetic Field and Melatonin on Testis Torsion and Detorsion Induced Rats Indicated by Scintigraphy, Positron Emission Tomography/Computed Tomography and Histopathological Methods - Gul, Serdar Savas; Gurgul, Serkan; Uysal, Murat; Erdemir, Fikret (Urology Journal, 2018)
Purpose: The aim of the present study was to show the protective effect of pulsed magnetic field (PMF) application and melatonin administration on damage in testis in a one-sided torsion detorsion induced rat model using testicular scintigraphy with 99mTc pertechnetate, PET/CT with 18F-FDG and histopathological methods. Materials and Methods: Sixty male rats were used in the study; 30 rats were randomly divided into five groups for one day applications of sham control, torsion, melatonin, pulsed magnetic field (PMF) and melatonin plus PMF. Similarly, for one week group, the other 30 rats were divided into the same five group (n=6), but the animals were sacrificed after one week. Rats were exposed to 50 Hz, 1 mT PMF for two hours. PET/CT with 37 MBq 18F-FDG and testicular scintigraphy with and 37 MBq 99mTc pertechnetate examinations were carried out, and testicular tissue was examined using histopathological methods. Results: In one day treatment, melatonin administration significantly increased perfusion and glucose metabolism compared to torsion group (p<0.01). Perfusion and glucose metabolism was also higher in the PMF and melatonin plus PMF groups than torsion group (p<0.01). In one week treatment, melatonin administration resulted in a significant higher perfusion rate and glucose metabolism rate compared to torsion group (p<0.01 and p<0.001, respectively). In addition, perfusion and glucose metabolism significantly increased in PMF and melatonin plus PMF groups compared to torsion group (p<0.01 and p<0.001, respectively). Furthermore, caspase-3 immunoreactivity and pathological changes increased in the torsion group (p<0.05). Melatonin and melatonin plus PMF treatment reduced the rate of immunoreactivity and pathological findings compared to the torsion group (p<0.05). Conclusion: According to these results it can be concluded that PMF application had a therapeutic benefit as effective as melatonin administering. In addition, it was indicated that PET/CT with 18F-FDG and testicular scintigraphy with 99mTc pertechnetate could be efficiently used in determining the treatment efficiency in testicular torsion.